Traditional and molecular analyses for fecal indicator bacteria in non-point source subtropical recreational marine waters - Sinigalliano, Christopher D.; Fleisher, Jay M.; Gidley, Maribeth L.; Solo-Gabriele, Helena M.; Shibata, Tomoyuki; Plano, Lisa R.W.; Elmir, Samir M.; Wanless, David; Bartkowiak, Jakub; Boiteau, Rene; Withum, Kelly; Abdelzaher, Amir M.; et al. (Water research (Oxford), 2010)
The use of enterococci as the primary fecal indicator bacteria (FIB) for the determination of recreational water safety has been questioned, particularly in sub/tropical marine waters without known point sources of sewage. Alternative FIB (such as the Bacteroidales group) and alternative measurement methods (such as rapid molecular testing) have been proposed to supplement or replace current marine water quality testing methods which require culturing enterococci. Moreover, environmental parameters have also been proposed to supplement current monitoring programs. The objective of this study was to evaluate the health risks to humans from exposure to subtropical recreational marine waters with no known point source. The study reported symptoms between one set of human subjects randomly assigned to marine water exposure with intensive environmental monitoring compared with other subjects who did not have exposure. In addition, illness outcomes among the exposed bathers were compared to levels of traditional and alternative FIB (as measured by culture-based and molecular-based methods), and compared to easily measured environmental parameters. Results demonstrated an increase in self-reported gastrointestinal, respiratory and skin illnesses among bathers vs. non-bathers. Among the bathers, a dose–response relationship by logistic regression modeling was observed for skin illness, where illness was positively related to enterococci enumeration by membrane filtration (odds ratio = 1.46 [95% confidence interval = 0.97–2.21] per increasing log10 unit of enterococci exposure) and positively related to 24 h antecedent rain fall (1.04 [1.01–1.07] per increasing millimeters of rain). Acute febrile respiratory illness was inversely related to water temperature (0.74 [0.56–0.98] per increasing degree of water temperature). There were no significant dose–response relationships between report of human illness and any of the other FIB or environmental measures. Therefore, for non-point source subtropical recreational marine waters, this study suggests that humans may be at increased risk of reported illness, and that the currently recommended and investigational FIB may not track gastrointestinal illness under these conditions; the relationship between other human illness and environmental measures is less clear.